KONTROL GETARAN GAGAL – AMAN MENGGUNAKAN PEMBANGKIT GAYA AKTIP - Satrijo, Djoeli (ROTASI, 2001)
Using the concept of force generators, various active vibration configurations have been axamined for theirperformance potential. It is shown that an active vibration control system offers a great deal of flexibility in that by aproper choice of active companent its transmisibility characteristics can be altered to suit the requirements. It is alsoshown how the full potential of active systems can be achieved even when there are passive components. An activesystem is designed in such a way that it gives the desired performance even in the event of the failure of the activecomponents through the reliability offered by a passive system.